Why language matters: Inequality perceptions among the Sámi in Sweden and Norway - Anika Lloyd-Smith; Fabian Bergmann; Yair Sapir; Rusen Yasar; Tanja Kupisch (University of Konstanz, Cluster of Excellence "The Politics of Inequality", Das Progressive Zentrum e.V., 2023)
Every two weeks, one of the world's estimated 7,000 languages dies. Yet what are the consequences of having to give up one's native language? Speakers of minority languages worldwide face barriers to using their languages outside their homes, often with negative consequences for educational and economic success. A new survey of the Indigenous Sámi in Sweden and Norway suggests that language policies are key to perceptions of inequality. Speakers of the Sámi languages have lower perceptions of their societal standing than Sámi who have given up the language. Combined with insights from an in-depth study on Sámi language education, our findings suggest that policies should facilitate language maintenance in linguistic minorities. Supporting these languages may help to reduce feelings of discrimination.
urn:nbn:de:bsz:352-2-toyyooc8zspe0
Keywords: 320